(untitled) (Journal of the College of Basic Education, 2023)
Education is an organized, purposeful process that seeks an end that is linked to the needs and requirements of the learner.on the one hand, and the objectives of the educational institution in which he is studying on the other hand, and he intends to plan toIncreasing the learners’ experiences of knowledge, information and skills to enrich their lives.Through the selection of appropriate educational materials, their mental abilities and sensory perceptions, which are based onModern methods and methods.